BIMG-02. IMAGING IMMORTALITY: TERT EXPRESSION ALTERS GLUCOSE METABOLISM IN LOW-GRADE GLIOMAS IN A MANNER THAT CAN BE LEVERAGED FOR NONINVASIVE METABOLIC IMAGING. (25th March 2021) - Viswanath, Pavithra; Batsios, Georgios; Gillespie, Anne Marie; Luchman, Hema Artee; Costello, Joseph; Pieper, Russell; Ronen, Sabrina
Abstract: Telomerase reverse transcriptase (TERT) is essential for tumor immortality and uncontrolled proliferation, including in low-grade oligodendrogliomas (LGOGs). Since it is silenced in somatic cells, TERT is also a therapeutic target. Non-invasive imaging of TERT can differentiate tumor from normal brain or lesions such as gliosis and allow assessment of response to therapy. The goal of this study was to identify magnetic resonance spectroscopy (MRS)-detectable metabolic alterations associated with TERT that can be leveraged for noninvasive imaging in LGOGs. We examined patient-derived BT54 neurospheres in which TERT expression was silenced by RNA interference. 1 H-MRS showed that steady-state levels of NAD(P)/H, glutathione, aspartate and AXP were elevated in BT54TERT+ neurospheres relative to BT54TERT- . Glucose flux through the pentose phosphate pathway (PPP) is essential for generating NADPH, which maintains glutathione homeostasis. 13 C-MRS confirmed that [2- 13 C]-glucose flux through the PPP was elevated in BT54TERT+ neurospheres relative to BT54TERT-, an effect associated with higher activity of the PPP enzyme glucose-6-phosphate dehydrogenase (G6PDH). Hyperpolarized 13 C-MRS is a method of increasing the signal to noise ratio of 13 C-MRS such that it can monitor metabolic fluxes noninvasively in cells, animals and patients. Consistent with elevated PPP flux and G6PDH activity, hyperpolarized [U- 13 C]-glucose metabolism via the PPP to 6-phosphogluconate (6-PG) was elevated in BT54TERT+ neurospheres relative to BT54TERT- . Importantly, examination of an additional patient-derived LGOG model, the SF10417 model which readily forms orthotopic tumor xenografts in rats, showed that 6-PG production from hyperpolarized [U- 13 C]-glucose demarcated tumor from normal brain. Furthermore, LGOG patient biopsies had elevated NAD(P)/H, glutathione, aspartate, AXP and G6PDH activity relative to gliosis biopsies, confirming the clinical validity of our observations. Collectively, we have identified a metabolic signature of TERT expression that can be leveraged via hyperpolarized [U- 13 C]-glucose to improve diagnosis and treatment response monitoring for LGOG patients.